Adaptive colour restoration and detail retention for image enhancement. Issue 14 (12th May 2021) - He, Kangjian; Tao, Dapeng; Xu, Dan
Abstract: Computer vision‐based crowd understanding and analysis technology has been widely used in public safety due to the rapid growth of population and the frequent occurrence of various accidents. Improving imaging quality is the key to improve the performance of crowd analysis, density estimation, target recognition, segmentation, and detection in computer vision tasks. Due to the complex imaging environment such as fog and low illumination, some images taken in outdoor environment often have the problems of colour distortion, lack of details, and the poor imaging quality, which affect the subsequent visual tasks. To improve the imaging quality and visual effect, an adaptive colour restoration and detail retention‐based method is proposed for image enhancement. First, to overcome the problem of colour distortion caused by low illumination and fog, a multi‐channel fusion based adaptive image colour restoration method is proposed. To make the enhancement result more consistent with human observation, the detail retention‐based method is applied to enhance the details. Experimental results demonstrate that the authors' results are effective and outperform the compared methods both in visual and objective evaluations.